Parent-adolescent conflict: an exploration from the perspective of Vietnamese adolescents - Nguyen, Thi Hong Hanh; Nguyen, Thi Nhu Trang (Frontiers in Psychology, 2023)
This research investigates parent-adolescent conflicts from the viewpoint of Vietnamese adolescents. Employing a mixed-method approach, the study conducted in-depth interviews and a questionnaire survey with 706 high-school students. The findings highlight that conflicts between Vietnamese parents and adolescents commonly arise regarding internet usage for entertainment and academic purposes. Furthermore, adolescents reported having more conflicts with their mothers than with their fathers. Although instances of parental aggression were identified, most adolescents perceived their parents' conflict resolution as supportive. However, Vietnamese adolescents tended to display passive behavioral responses during conflicts. The research also identified certain emotional responses as warning signs of mental health issues, including suicidal thoughts, among some adolescents. Moreover, a higher frequency of conflicts with parents was significantly associated with increased peer connections. The study emphasizes the importance of professionals, such as school social workers or counselors, prioritizing the understanding of parent-child conflicts' impact on adolescents' emotions and mental health. Additionally, it underscores the significance of examining parenting patterns and parent-child communication within contemporary Vietnamese families.